Evaluation of the Louvre Abu Dhabi interactive website: user perceptions, usability, and learning outcomes - Mallek, Mohamed; Mohamed, Elsir; Mohamed, Widad; Jeljeli, Riadh; Hamid, Abdulazim (Frontiers in Human Dynamics, 2025)
IntroductionThis study evaluates user perceptions of the Louvre Abu Dhabi (LAD) interactive website, focusing on how digital technologies influence the consumption and interpretation of cultural heritage.MethodsThe research employed a mixed-method design with 50 participants. It investigated key parameters including usability, content richness, and learning outcomes, specifically examining how digital interactivity supports heritage engagement. The analytical framework extended the Technology Acceptance Model (TAM) and the Kano model to a Gulf cultural context.ResultsFindings revealed consistently high satisfaction across usability and learning dimensions, confirming the site’s effectiveness as a cultural mediation tool. Beyond technical performance, participants described the platform as a gateway to immersive and participatory heritage consumption, where digital storytelling and interactivity foster curiosity and sustained cultural interest.DiscussionThematic analysis identified key development priorities: immersive virtual and augmented reality (VR/AR) integration, deeper narrative context, personalized guided itineraries, and stronger social-media outreach. The results suggest that digital heritage features have evolved from optional enhancements to essential components of cultural participation. The study concludes that sustained innovation in immersive design and AI-driven personalization is vital for museums seeking to expand cultural access and learning through digital media.